LBP-1.03 "No one was there to care for us" Ashraya's response to its members' needs in terms of care and support. (10th July 2011) - Chevrier, C
Abstract : Background: Sex workers (SWs) have been identified as a "high-risk group" and considerable effort has been invested in promoting "safer sex" among this group. However, their specific concerns and identities vanish in broader public health policy discussions related to treatment and particularly care. Ashodaya Samithi, a SWs organisation based in Mysore, Karnataka, has been providing extensive care and support (C&S) services to SWs and "non-SWs" living with HIV through their sub-wing organisation, Ashraya, since 2008. Considering the enduring stigma attached to SWs, what motivates individuals to seek health services from Ashraya? Methods: 40 in-depth interviews (including 10 with non-SWs) were conducted with Ashraya members in 2011 to explore how Ashraya responds to the needs of its members in terms of C&S. Content analysis of the transcripts was completed to sort out themes. Results: Analysis shows that in spite of scarce resources, the accessibility, effective outreach efforts, and commitment and reliability of Ashraya's volunteers are major components of its growing popularity. Conclusions: In the near-absence of non-discriminatory, affordable C&S for people living with HIV/AIDS, Ashraya offers much needed relief to its members. The potential role of SWs community-based organisations in providing C&S, which goes beyond safer sex promotion, needs to be accounted for within national-level policy planning and in evaluating existing programs.